2007
DOI: 10.1007/s00330-007-0650-x
|View full text |Cite
|
Sign up to set email alerts
|

Two K versus 4 K storage phosphor chest radiography: detection performance and image quality

Abstract: The purpose of this study was to evaluate the effect of matrix size (4-K versus 2-K) in digital storage phosphor chest radiographs on image quality and on the detection of CT-proven thoracic abnormalities. In 85 patients who underwent a CT of the thorax, we obtained two additional posteroanterior storage phosphor chest radiographs, one with a matrix size of 3,520x4,280 (=4-K) and the other with a matrix size of 1,760x2,140 (=2-K). Acquisition, processing and presentation parameters were identical for all radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…These experimental data explain that a number of clinical studies could not find an advantage of 4k matrices for detection of a broad range of intrapulmonary lesions [ 12 , 13 ], delineation of anatomical landmarks [ 13 ] or interstitial diseases [ 14 ].…”
Section: Developments In Detector and Readout Technologymentioning
confidence: 99%
“…These experimental data explain that a number of clinical studies could not find an advantage of 4k matrices for detection of a broad range of intrapulmonary lesions [ 12 , 13 ], delineation of anatomical landmarks [ 13 ] or interstitial diseases [ 14 ].…”
Section: Developments In Detector and Readout Technologymentioning
confidence: 99%
“…Giger and Doi (1987) calculated signal-to-noise (SNR) based on signal detection theory, and found that 200 μm pixel is adequate for detail detection in most digital radiography examinations. Following the introduction of CR devices, it was found that switching from 200 to 100 μm pixels did not improve performance for the detection of intrapulmonary lesions (Koelblinger et al 2007). This was attributed to the poor modulation transfer function (MTF) and detective quantum efficiency (DQE) of the CR powder phosphor plates at spatial frequencies above 2.5 mm −1 Flynn 2002, Schaefer-Prokop et al 2008).…”
Section: Introductionmentioning
confidence: 99%